Severe adenovirus pneumonia complicated by acute respiratory distress syndrome in immunocompetent patients: a case report and literature review - Zhang, Lei; Guo, Yuxin; Wang, Xudong; Gai, Wei; Liu, Lina (Frontiers in Medicine, 2025)
BackgroundHuman adenovirus (HAdV) is one of the most important pathogens detected in acute respiratory illness in pediatric and immunocompromised patients, but it is relatively rare to develop severe pneumonia in immunocompetent patients. We analyzed the clinical features, as well as the diagnosis and treatment processes, to provide a reference for clinical practice.Case presentationWe report a case of severe pneumonia caused by HAdV, complicated by acute respiratory distress syndrome (ARDS), in an immunocompetent patient with no underlying conditions. Chest computed tomography (CT) revealed consolidation in the right lower lung. Conventional microbial tests were negative, but metagenomic next-generation sequencing (mNGS) identified a large number of HAdV sequences in blood and sputum. Together with the clinical symptoms, this confirmed the diagnosis of severe pneumonia caused by HAdV. The patient was discharged after timely treatment with cidofovir.ConclusionIn our study, we described a rare case of severe pneumonia caused by HAdV, complicated by ARDS, in an immunocompetent patient. mNGS proves to be an effective diagnostic tool for guiding treatment decisions.